VISUALIZATION TECHNOLOGIES IN THE STUDY OF COMPUTER SCIENCE BY UNIVERSITY STUDENTS: IMPROVEMENT OF EDUCATIONAL SUCCESS - Stepanova, Julia; Mikhailovich , Igor; Kudryashova, Nina; Igorevna , Diana; Belobragin, Vitaliy (Revista Inclusiones, 2020)
The rapid penetration of ICT into human life and the overload of information flows require modern education to adopt new technologies, change educational methods, present educational information, and introduce new educational technologies that would be effective in today's conditions. This article shows the relevance of the educational process visualization, characterizes visualization technologies as a tool to increase the success of learning, determines the essence of visualization in education, and gives a description of virtualization as one of the technological trends in the visualization of education. Due to the experimental study of the use of virtualization technologies of operating systems in the discipline "Computer Science Fundamentals", it is concluded that their use leads to the increase in the success of student learning.